TRANSLANGUAGING AS A PEDAGOGICAL STRATEGY IN EFL CLASSROOM A THEMATIC LITERATURE REVIEW ON LEARNING OUTCOMES AND CLASSROOM PRACTICES - Pratiwi, Made Yulia Anindita (UHN IGB Sugriwa Denpasar, 2025)
This study’s main focus is the most recent literature, published in 2020-2025, which represents the use of translanguaging as a teaching strategy in the English as a Foreign language classrooms. Nevertheless, translanguaging has gained popularity for its potential to support multilingual learners, many of the teachers still lack of guidance on how to implement it systematically. To address this gap, this study employed a thematic literature review of eight empirical articles selected across major academic database through strict inclusion and exclusion criteria. The research objective is to identify how translanguaging is practiced in EFL classrooms across various contexts, and what impact it has on EFL learning outcomes and classroom activities. The literature is pulled from a variety of journal articles related to the topic of the translanguaging, learning, and teaching in a multilingual framework. The final results pointed out that the use of translanguaging in the classroom has facilitated student’s lesson comprehension, language comprehension, eliminates language anxiety and increases engagement. It helps the teacher to explain challenging information, learn student backgrounds, and connect the lesson to their personal life. However, it also showed several constraints namely teacher unpreparedness, school restrictions on language use, and student reliance on the first language. Therefore, the application of translanguaging has benefits and cons to the language teacher and students, thus it’s effective use should be encouraged. This study contributes a synthesized overview of learning outcomes and classroom practices across diverse context by offering a clearer map of translanguaging’s pedagogical value and its practical challenges. It suggests that additional teacher education on the matter is needed, and schools should allow a more lenient stimulation. Thus, this method can be successfully applied, because it is active and efficient.